2011
DOI: 10.1016/j.contraception.2011.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to dual-method contraceptive use

Abstract: Background Patient characteristics associated with adherence to dual method contraceptive use are not known. Study Design Project PROTECT was a 24-month long randomized trial designed to promote the use of dual methods of contraception using an individualized computer-based intervention or enhanced standard care counseling intervention. We analyzed 463 women with follow-up data and examined sustained dual method use (reported at 2+ interviews). Results While 32% initiated dual method contraceptive use, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…While our findings are consistent with a growing body of literature in the general population linking mental illness to inconsistent contraceptive use [24,25,[31][32][33][34], prior studies among Veterans report conflicting findings [21,22]. One study examining predictors of poor adherence using national N= 9780 women, except as noted above.…”
Section: Discussionsupporting
confidence: 65%
“…While our findings are consistent with a growing body of literature in the general population linking mental illness to inconsistent contraceptive use [24,25,[31][32][33][34], prior studies among Veterans report conflicting findings [21,22]. One study examining predictors of poor adherence using national N= 9780 women, except as noted above.…”
Section: Discussionsupporting
confidence: 65%
“…The purpose of this analysis was to evaluate the impact LARC initiation had on condom use as well as rates of incident STIs. Our data, consistent with previously published studies, reaffirms that consistent condom use and dual contraceptive method use are low (5, 10, 11, 21) regardless of which additional contraceptive method is being used. Data from the 2006–2008 NSFG survey found 7.3% of women using any contraceptive method reported dual-method use at their most recent intercourse in the previous 12 months (10).…”
Section: Commentssupporting
confidence: 92%
“…Clinicians have long recommended dual protection with an effective contraceptive method along with condom use. Poor adherence to these recommendations poses a challenge to reliable prevention of both STIs and pregnancy (5–7, 10, 11). Several studies have suggested that rates of dual­method use among LARC users is lower than among users of other short acting reversible methods (10, 1215).…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of dual method use among American women ranges from 7% to 38%. [2][3][4][5][6][7] A handful of studies on dual protection have been conducted in Sub-Saharan Africa, where both HIV and unwanted pregnancy are critical public health challenges. In South Africa and Botswana studies, dual method use at last sex ranged from 4% to 28%.…”
mentioning
confidence: 99%